Convergence of the Gold and Green Roads at Scholarly Communication and Reflections on Turkey - Ertürk, Korhan Levent; Şengül, Gökhan (Information World, 2011)
In parallel with the increase of information exchange rate in social networks and the usage of mobile communication devices in recent years, it is also required that the information needs to be shared and freely accessable in different enviroments. In this context freely access to the papers including scientific findings by other scientists and broad population will help to increase both the accuracy and reability of the papers. Besides it will also affect positively the information sharing and scientific improvements. The open access initiative made a great contribution to this object in last ten years. For this purpose self archiving (green road) and open access journal (golden road) are presented as new methods to present scientific research results to community.In this study the rules about the green and golden roads in international area is examined first, and adaptation of authors and publishers to golden and green roads are investigated. Then adaptation of Turkey’s instutional archives and journals about the golden and green roads are also evaluated. In this study Ulrichsweb, Thomson Reuters Web Of Science (WoS) and Elsevier Scopus databases, RoMEO, Juliet and ROARMAP guides, OpenDOAR, ROAR instutional archives and DOAJ open access journal guidence, and finally ULAKBİM national databases are analysed.
Keywords: Scholarly communication; Open access; Institutional repositories; Open access journals; Citation indexes